Analisis Efektivitas Realisasi Anggaran Pendapatan Belanja Daerah Kota Medan Tahun 2021-2023 - Rinaldi Rinaldi; Alawi Parkindungan Hasibuan; Putri Kemala Dewi Lubis; Jelita Simanungkalit (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Medan city is one of the largest cities in Indonesia. The increasing need for infrastructure amidst the increasing population in the city of Medan is a challenge that must be resolved. This research was conducted to evaluate the effectiveness of the Medan City Revenue and Expenditure Budget considering that the budget allocation for improving infrastructure that has been carried out by the Medan City Government is the government's priority. The research method used in this research is a descriptive analysis method with a qualitative approach. The results of the research found that effectiveness in managing the APBD is still less effective. In this case, the effectiveness of budget management still needs to be improved so that fund allocation can be optimized and create more inclusive and sustainable development.